Mechanical impact in disk mill for producing controlled rice husk particle size by changing impactor shapes and disk rotation speeds Kesan mekanikal di kilang cakera untuk menghasilkan saiz zarah sekam padi terkawal dengan mengubah bentuk impak dan kelajuan putaran cakera - Nandiyanto, A.B.D. (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this study was to evaluate regulation of mechanical impact (i.e. impactor sizes and shapes) on triangle, cylinder, and cube as well as disk rotation speed (from 600 to 1500 rpm) in disk mill for controlling size-reduction process. As a model of size-reduced material, rice husk was selected. The study was done by evaluating the final milling product size, which was completed by the measurement of energy impact during the milling process. Experimental results showed that the product size was controllable in the range of between 50 and 1000 Î¼m. The impactor sizes and shapes influenced the contact diameter and area of impactor for making more materials being collided, whereas disk rotation speed led to giving more collision number (between rice husk and impactor) and increasing impact from the collision (due to less time contact during collision). This study provides an important information, which can be further generalized in the use of milling process as a tool for materials size-reduction and mechanochemical process. Â© 2020 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.